Dampak Pandemi Covid-19 terhadap Peran Guru Bimbingan dan Konseling pada Siswa di Mts Fatahillah Semarang - Tatum Arisya Akmala; Nadilla Anngiana Fahri Yuyun Marsela; Mufa Rikah; Wahyuni Tri Ernawati (SHINE: JURNAL BIMBINGAN DAN KONSELING, 2021)
The COVID-19 pandemic, which has hit almost all parts of the world, has forced to change the state of the world, not education. Activities are carried out boldly (in the network), not counseling guidance. The results showed that the services provided by Guidance and Counseling teachers during the COVID-19 pandemic at MTs Fatahillah were in the form of information services, orientation services, classical services, group guidance, group counseling, and case transfer services (referrals). The purpose of this study was to determine the impact of the COViD-19 pandemic on students at Mts Fatahillah Semarang. The method used is descriptive qualitative by using interview media and filling out google forms. Furthermore, the results of the analysis using a literature review in accordance with the subject.Keywords: Guidance counseling, school, COVID-19